PENGEMBANGAN KAWASAN WISATA SITU TANDON CIATER DENGAN KONSEP RAMAH LINGKUNGAN, DI KOTA TANGERANG SELATAN - Ongko Rizal Juzali; Tri Endangsih (MAESTRO, 2019)
The development of the Tandon Ciater Situ Tourism Area is an effort to make the tourism area environmentally friendly. Where also makes the tourist area not only provide recreational facilities to relieve fatigue, or adrenaline, such as outbound tours, water tourism, camping ground, playground, jogging track and food court but also provides learning facilities such as agricultural education tours, workshops recycling, and how to preserve the surrounding environment specifically intended for residents around the Situ Tandon Ciater Tourism Area. So the learning activities provided are in the form of understanding how to grow crops, harvest crops, and also how to make recycled materials into a high-value work. The building of Situ Tandon Ciater Tourism Area Development carries the concept of Environmental Friendly Architecture. The concept of environmentally friendly architecture is the concept of an architectural environmental awareness that not only incorporates the main aspects of architecture (strong, functional, comfortable, low cost, and aesthetic), but also incorporates the environmental aspects of a Green Building, energy efficiency, sustainable concepts and approaches holistic towards the environment that includes harmony between humans and their natural environment. So later the application of Environmentally Friendly Architecture at the time of the building in the Tandon Ciater Tourism Area in the form of environmentally friendly material, energy utilization or existing land acquisition, and also did not escape provide aesthetics for building users, especially facilities developed.